Virtual Local Area Network for Optimizing Network Performance using Simplified Form of Action Research - Abdillah, Muhammad Fahmi; Wijayanto, Agus; Pamungkas, Wisnu Hera (Politeknik Negeri Batam, 2025)
Virtual Local Area Network (VLAN) is an effective solution for improving network performance and efficiency in educational environments, particularly in computer laboratories. This study aims to implement and evaluate VLAN at the Computer Laboratory of Universitas Mulia using a simplified action research approach involving a single intervention cycle. The initial diagnosis revealed that the conventional flat network topology resulted in a broad broadcast domain and reduced performance under high traffic conditions. Through VLAN segmentation, the laboratory was logically divided into five segments based on functionality. Evaluation was conducted using throughput measurement and Quality of Service (QoS) indicators, including packet loss, delay, and jitter, based on TIPHON standards. The results indicated consistent improvements in data flow and stability, with reduced packet loss under 0,3% and average delay and jitter remaining below 20 ms across all segments. In addition to technical improvements, interviews with the network administrator highlighted significant benefits in bandwidth management and traffic control during examinations. This study demonstrates that a simplified approach can be replicated in similar educational institutions with limited resources and provides a foundation for more structured and controlled network development.